Editorial based on: “Risk of dementia in adults with congenital heart disease: population-based cohort study” - Mebius, Mirthe J.; Roofthooft, Marcus T. R.; Bos, Arend F. (Journal of Thoracic Disease, 2018)
The cardiovascular system is one of the first to develop in the human fetus. Due to its complexity, cardiogenesis is a process susceptible to mistakes. Congenital heart disease (CHD), therefore, is a common human birth defect with a prevalence of 5 to 12 per 1,000 live births (1). Over the last decades, treatment of CHD has improved tremendously and nowadays, almost all infants with CHD reach adulthood.